2002
DOI: 10.1007/s001980200021
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-masked, 2-year Comparison of Tibolone with 17β-Estradiol and Norethindrone Acetate in Preventing Postmenopausal Bone Loss

Abstract: In this 2-year, randomized study, we compared the efficacy and tolerability of tibolone 2.5 mg (n = 75), tibolone 1.25 mg (n = 76) and estradiol 2 mg plus norethindrone acetate 1 mg (E2/NETA: n = 74) for preventing bone loss in postmenopausal women. Bone mineral density (BMD), measured by dual-energy X-ray absorptiometry, and bone remodeling markers were assessed every 6 months. Side-effects were assessed quarterly. After 24 months, the mean increase (+/- SD) in lumbar spine BMD from baseline was 3.6% +/- 2.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 52 publications
0
14
0
5
Order By: Relevance
“…T can even prevent bone loss due to Gonadotropin releasing hormone (GnRH)-agonist administration in young women [32]. Overall, several randomised, PL-and active-controlled studies have shown that T is effective in preserving and/or increasing BMD and preventing bone loss and osteoporosis [33,34] in early and late PMW and even when osteoporosis is already established [35]. T (1.25 mg/day), in comparison with PL, can decrease the relative hazard of osteoporosis-related vertebral and non-vertebral fractures in older PMW during a median of 34 months of treatment (LIFT study) [9].…”
Section: Tibolone and Bonementioning
confidence: 99%
“…T can even prevent bone loss due to Gonadotropin releasing hormone (GnRH)-agonist administration in young women [32]. Overall, several randomised, PL-and active-controlled studies have shown that T is effective in preserving and/or increasing BMD and preventing bone loss and osteoporosis [33,34] in early and late PMW and even when osteoporosis is already established [35]. T (1.25 mg/day), in comparison with PL, can decrease the relative hazard of osteoporosis-related vertebral and non-vertebral fractures in older PMW during a median of 34 months of treatment (LIFT study) [9].…”
Section: Tibolone and Bonementioning
confidence: 99%
“…Both conditions are often concomitant and seem to be more pronounced with increasing postmenopausal years. Tibolone, as an alternative to hormone replacement therapy (HRT), has been reported to increase the severity of diffuse alopecia and possibly induce facial hypertrichosis [27]. Frontal fibrosing alopecia (FFA) is a distinct condition probably accentuated by menopause, although it is not controlled by HRT.…”
Section: Hair Follicles During Climactericmentioning
confidence: 99%
“…Wśród badanych kobiet 7-9% podaje obecność bardzo uciążliwych objawów wazomotorycznych w postaci silnych uderzeń gorąca (7 i więcej epizodów w ciągu doby) [2]. Najskuteczniejszą formą leczenia objawów menopauzalnych jest niewątpliwie terapia hormonalna (hormonal therapy -HT) [3][4][5]. W świetle obecnej wiedzy głównymi wskazaniami do jej zastosowania są umiarkowane i silne objawy naczynioruchowe, atrofia urogenitalna, pogorszenie jakości życia oraz profilaktyka osteoporozy u pacjentek z przedwczesną menopauzą.…”
Section: Wstępunclassified